'Information on the fly': Challenges in professional communication in high technological nursing. A focus group study from a radiotherapy department in Sweden - Widmark Catarina; Tishelman Carol; Gustafsson Helena; Sharp Lena (BMC, 2012)
Abstract Background Radiotherapy (RT) units are high-tech nursing environments. In Sweden, RT registered nurses (RNs) provide and manage RT in close collaboration with other professional groups, as well as providing nursing care for patients with cancer. Communication demands on these RNs are thus particularly complex. In this study, we aimed to better understand problems, strengths and change needs related to professional communication with and within the RT department, as a basis for developing a situation-specific intervention. Methods Focus groups discussions (FGDs) were conducted with different professional (RNs, assistant nurses, physicians, engineers and physicists) and user stakeholders. Transcripts of the FGDs were inductively analyzed by a team of researchers, to generate clinically relevant and useful data. Results These findings give insight into RT safety climate and are presented under three major headings: Conceptualization of professional domains; Organization and leadership issues; and Communication forms, strategies and processes. The impact of existing hierarchies, including how they are conceptualized and acted out in practice, was noted throughout these data. Despite other differences, participating professionals agreed about communication problems related to RT, i.e. a lack of systems and processes for information transfer, unclear role differentiation, a sense of mutual disrespect, and ad hoc communication taking place 'on the fly'. While all professional groups recognized extensive communication problems, none acknowledged the potential negative effects on patient safety or care described in the FGD with patient representatives. While RNs often initially denied the existence of a hierarchy, they placed themselves on a hierarchy in their descriptions, describing their own role as passive, with a sense of powerlessness. Potential safety hazards described in the FGDs include not reporting medical errors and silently ignoring or actively opposing new guidelines and regulations. Conclusions There is a risk that RNs who view themselves as disenfranchised within an organization will act with passive resistance to change, rather than as change promoters. As interventions to strengthen teams cannot be stronger than the weakest link, RNs may need support in the transition "from silence to voice" in order to take a position of full professional responsibility in a multi-professional health care team.